The in-vitro effect of famotidine on SARS-CoV-2 proteases and virus replication - Loffredo, Madeline; Lucero, Hector; Chen, Da-Yuan; O’Connell, Aoife; Bergqvist, Simon; Munawar, Ahmad; Bandara, Asanga; De Graef, Steff; Weeks, Stephen D.; Douam, Florian; Saeed, Mohsan; Munawar, Ali H. (Scientific reports, 2021)
The lack of coronavirus-specific antiviral drugs has instigated multiple drug repurposing studies to redirect previously approved medicines for the treatment of SARS-CoV-2, the coronavirus behind the ongoing COVID-19 pandemic. A recent, large-scale, retrospective clinical study showed that famotidine, when administered at a high dose to hospitalized COVID-19 patients, reduced the rates of intubation and mortality. A separate, patient-reported study associated famotidine use with improvements in mild to moderate symptoms such as cough and shortness of breath. While a prospective, multi-center clinical study is ongoing, two parallel in silico studies have proposed one of the two SARS-CoV-2 proteases, 3CL pro or PL pro , as potential molecular targets of famotidine activity; however, this remains to be experimentally validated. In this report, we systematically analyzed the effect of famotidine on viral proteases and virus replication. Leveraging a series of biophysical and enzymatic assays, we show that famotidine neither binds with nor inhibits the functions of 3CL pro and PL pro . Similarly, no direct antiviral activity of famotidine was observed at concentrations of up to 200 µM, when tested against SARS-CoV-2 in two different cell lines, including a human cell line originating from lungs, a primary target of COVID-19. These results rule out famotidine as a direct-acting inhibitor of SARS-CoV-2 replication and warrant further investigation of its molecular mechanism of action in the context of COVID-19.